2013
DOI: 10.1371/journal.pone.0063021
|View full text |Cite
|
Sign up to set email alerts
|

Shared Effects of Genetic and Intrauterine and Perinatal Environment on the Development of Metabolic Syndrome

Abstract: Genetic and environmental factors, including the in utero environment, contribute to Metabolic Syndrome. Exposure to high fat diet exposure in utero and lactation increases incidence of Metabolic Syndrome in offspring. Using GLUT4 heterozygous (G4+/−) mice, genetically predisposed to Type 2 Diabetes Mellitus, and wild-type littermates we demonstrate genotype specific differences to high fat in utero and lactation. High fat in utero and lactation increased adiposity and impaired insulin and glucose tolerance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 76 publications
3
51
1
1
Order By: Relevance
“…The CD1 mouse model is an outbred strain and was chosen because of a strong heterogeneity in its genome [27]. WT female mice were bred to non-littermate GLUT4 heterozygote (G4+/-) males [28, 29]. Genotyping was performed as previously described [30].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD1 mouse model is an outbred strain and was chosen because of a strong heterogeneity in its genome [27]. WT female mice were bred to non-littermate GLUT4 heterozygote (G4+/-) males [28, 29]. Genotyping was performed as previously described [30].…”
Section: Methodsmentioning
confidence: 99%
“…Male offspring were the focus of this study to circumvent the confounding effects of estrogen in metabolism. In addition, we previously demonstrated that only male offspring exposed to HFD during IU/L develop hypertension in adult life [28]. Body weight was recorded weekly until 12 weeks of life and then bi-weekly until the end of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased globalization, associated with a nutritional transition towards Western diets, is thought to be a contributing factor to the increasing prevalence of obesity and T2D globally (Popkin 2006)). In addition to poor diet and genetics, evidence suggests that an altered intrauterine environment (IU) plays a key role in the development of MetS (Vuguin, et al 2013) and that interactions between the IU environment and lifestyle can increase risk of MetS and T2D in people who are genetically susceptible (Hu 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Poor nutrition during pregnancy impacts fetal growth and development particularly that of the endocrine pancreas (Snoeck, et al 1990; Vuguin, et al 2013). Specifically, alterations in the IU environment caused by a low calorie, low protein or a high fat diet (HFD) affects the function of the endocrine pancreas by altering islet size, islet vascularization, number of insulin-cells (INS), insulin content, function, and parasympathetic innervation (Cerf, et al 2005; Dahri, et al 1991; Ford, et al 2009; Garofano, et al 1997; Ng, et al 2010; Rodriguez-Trejo, et al 2012; Vogt, et al 2014).…”
Section: Introductionmentioning
confidence: 99%